2020
DOI: 10.1186/s12889-020-09430-w
|View full text |Cite
|
Sign up to set email alerts
|

Multi-measure assessment of adherence to antiretroviral therapy among children under five years living with HIV in Jinja, Uganda

Abstract: Background: Adherence to Antiretroviral Therapy (ART) is required to achieve HIV viral load suppression. However, children under 5 years in Jinja, Uganda, had been shown to have low HIV suppression rates. This study aimed to determine the level of ART non-adherence among these children and the associated factors. Methods: Data for the cross-sectional study was collected from April to July 2019, from caregivers of 206 children under 5 years living with HIV who were attending health facilities in Jinja and had b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
4
1
Order By: Relevance
“…14 However, it was less than different researches done in Ethiopia which were 90% to 94%, 10-12 91% in Nigeria, 8 and 89.1% in South Africa. 7 However, the current study was higher than studies conducted in Fiche, Ethiopia which was 64.2%, 9 66.7% in Ambo (Ethiopia), 15 79.8% in South Sudan, 4 42.7% in Uganda, 16 and 47.5% in Ghana. 6 The discrepancies might be due to differences in the measurement of adherence assessment used and differences in clinical settings.…”
Section: Discussioncontrasting
confidence: 74%
“…14 However, it was less than different researches done in Ethiopia which were 90% to 94%, 10-12 91% in Nigeria, 8 and 89.1% in South Africa. 7 However, the current study was higher than studies conducted in Fiche, Ethiopia which was 64.2%, 9 66.7% in Ambo (Ethiopia), 15 79.8% in South Sudan, 4 42.7% in Uganda, 16 and 47.5% in Ghana. 6 The discrepancies might be due to differences in the measurement of adherence assessment used and differences in clinical settings.…”
Section: Discussioncontrasting
confidence: 74%
“…Numerous observational studies in adults support a link between food insecurity and poor treatment adherence [ 28 ], including work carried out in Zambia [ 29 ]. More recent research has suggested that children may likewise be affected [ 30 , 31 ]. In our study, we found no significant differences in antiretroviral therapy adherence among children in food insecure households.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in Uganda, Kenya, South Africa, Thailand, and the Netherlands have used various combinations of caregiver self-reports of missed doses, electronic dose monitoring, pill counts, and plasma or hair drug levels to measure and report on ART adherence. 5 , 13 15 Due to the high cost associated with its’ use, electronic dose monitoring is not feasible in every setting; however, it is considered to be a reliable measurement of medication adherence. 16 Medication event monitoring systems (MEMS ® ; Aardex Group Ltd., Seraign, Belgium, Switzerland) 17 pill bottle caps are commonly used for this purpose and record a time stamp of each time the pill bottle is opened in order report on how many doses are taken in a time period.…”
Section: Introductionmentioning
confidence: 99%
“…A more feasible and low-cost measurement of adherence is child and caregiver self-reports, as they don’t require any additional equipment, blood draws or for YLWH to bring medication into clinic. 13 , 14 , 18 20 Self-reports, however, introduce a risk of social desirability bias, in which individuals may over-report the number of doses taken out of a fear of reporting undesirable outcomes to researchers and clinicians. 21 While social desirability bias is somewhat intractable in research and clinical assessment, it may be mitigated by establishing trust and rapport with researchers or clinicians or using particular language in surveys and questionnaires, which may increase the validity of self-reports.…”
Section: Introductionmentioning
confidence: 99%